The Influence of Grit and Work Engagement on Work Readiness Mediated by Work Experience - Wulandari, Yulia Aisyah; Padmandtyo, Sri (Universitas Muhammadiyah Surakarta, 2024)
Purpose: Requirements for the qualities that individuals need to have in the workplace continue to develop and increase along with changes in needs and conditions in the work environment. This research aims to determine the influence of grit and work engagement on work readiness, with work experience acting as a mediator. Methodology: A quantitative approach was employed, with sample selection using probability sampling techniques, specifically Stratified Random Sampling. Data analysis was conducted using the SEM Smart PLS method. This study involved 226 respondents from the Soloraya area, surveyed through a questionnaire. Results: The results of the study showed that grit had a significant positive effect on work experience (T-statistic = 2.455, p = 0.014), and work engagement had a significant effect on work experience (T-statistic = 6.153, p < 0.001). In addition, work experience had a significant effect on work readiness (T-statistic = 9.877, p < 0.001). Applications/Originality/Value: This study highlights the importance of work experience as a mediator in the relationship between work engagement and work readiness. The findings indicate that grit and work engagement positively affect work readiness, with work experience serving as a mediator.